Evaluation of Climate Variability and Its Impact over East Asia in AMIP-type Simulation of the Korean Integrated Model - Sae-Rim Yeo; Eun-Hee Lee; Sang-Yoon Jun (Advances in Atmospheric Sciences, 2026)

Three distinct convective footprints over the Indo-western Pacific that affect high temperature extreme events in Korea during boreal autumn - Sae-Rim Yeo; Yun-Young Lee; Jong-Seong Kug (Climate Dynamics, 2022)

Summer climate variability over Korea in association with diverse features of ENSO evolution - Sae-Rim Yeo; Seon Tae Kim (Climate Dynamics, 2021)

The non-linear relationship between the western North Pacific anticyclonic circulation and Korean summer precipitation on subseasonal timescales - Sae-Rim Yeo; MinHo Kwon; June-Yi Lee (Climate Dynamics, 2020)

Development of the Expert Seasonal Prediction System: an Application for the Seasonal Outlook in Korea - WonMoo Kim; Sae-Rim Yeo; Yoojin Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Monthly climate variation over Korea in relation to the two types of ENSO evolution - Sae‐Rim Yeo; Sang‐Wook Yeh; Yoojin Kim; So‐Young Yim (International Journal of Climatology, 2018)
This study documents monthly temperature and precipitation anomalies over Korea during the different phases of El Niño‐Southern Oscillation (ENSO) for the two types of ENSO evolution. The evolution process of ENSO can be classified into two groups based on whether El Niño turns into La Niña in the subsequent year. The first group involves the transition process from El Niño to La Niña, while the second group shows the prolonged El Niño or neutral conditions after the mature phase of El Niño. Because the mid‐latitude atmospheric responses as well as the equatorial heating anomalies for the two groups of ENSO are different each other, the ENSO‐related climate variation over Korea are investigated separately for the two ENSO evolution groups. In particular, this study focuses on the entire monthly evolution of the temperature and precipitation over Korea during the different phases of ENSO. The statistically robust signals can be found in several particular months, which provides statistical basis for predicting monthly climate over Korea. In addition to the observational data analyses, we further investigate the forecast skill of the Asia‐Pacific Economic Cooperation Climate Center (APCC) Multi‐Model Ensemble (MME) in simulating two groups of ENSO evolution and their impacts on Korean climate. The result shows that the MME reasonably predicts the two different evolution of ENSO as in observation but their prediction skills for the ENSO‐related Korean climate are diverse, which largely depends on the phase of ENSO.

The role of low-frequency variation in the manifestation of warming trend and ENSO amplitude - Sae-Rim Yeo; Sang-Wook Yeh; Kwang-Yul Kim; WonMoo Kim (Climate Dynamics, 2017)

Eurasian snow cover variability in relation to warming trend and Arctic Oscillation - Sae-Rim Yeo; WonMoo Kim; Kwang-Yul Kim (Climate Dynamics, 2017)

Decadal changes in the Southern Hemisphere sea surface temperature in association with El Niño–Southern Oscillation and Southern Annular Mode - Sae-Rim Yeo; Kwang-Yul Kim (Climate Dynamics, 2015)

Global warming, low-frequency variability, and biennial oscillation: an attempt to understand the physical mechanisms driving major ENSO events - Sae-Rim Yeo; Kwang-Yul Kim (Climate Dynamics, 2014)

Recent climate variation in the Bering and Chukchi Seas and its linkages to large-scale circulation in the Pacific - Sae-Rim Yeo; Kwang-Yul Kim; Sang-Wook Yeh; Baek-Min Kim; Taehyoun Shim; Jong-Ghap Jhun (Climate Dynamics, 2014)

Intraseasonal variability of western North Pacific subtropical high based on the El Niño influence and its relationship with East Asian summer monsoon - Sae-Rim Yeo; Jong-Ghap Jhun; WonMoo Kim (Asia-Pacific Journal of Atmospheric Sciences, 2012)